Overexpression of TaPSKR1L-6A improves resistance to sharp eyespot and increases lignin accumulation in wheat - Qi, Haijun; Hao, Yuran; Zhu, Xiuliang; Zhang, Zengyan (Frontiers in Plant Science, 2025)
The soil-borne fungi Rhizoctonia cerealis is one of the major pathogens for the economically-important diseases sharp eyespot of common wheat (Triticum aestivum). Certain phytosulfokine receptor 1 (PSKR1) genes mediate resistance to diseases caused by biotrophic/hemibiotrophic pathogens in several plant species. Yet, none of wheat PSKR1 genes with positive effect on the innate immune responses to R. cerealis has been reported. Here, we characterize the phytosulfokine receptor 1-like gene TaPSKR1L-6A on wheat chromosome 6A, and determined functional role of it in wheat defense against R. cerealis. We used RNA-seq, BSMV-induced gene silencing and transgenic wheat to investigate the role of TaPSKR1L-6A in resistance to R. cerealis. The results showed that TaPSKR1L-6A has a resistance effect on R. cerealis. Transcription analysis showed that its expression level was upregulated when infected with sheath blight. Overexpression of TaPSKR1L-6A significantly increased sheath blight resistance, upregulated the expression of lignin synthesis and metabolism pathway genes, and increased lignin accumulation, which was opposite to the results of silencing TaPSKR1L-6A. Collectively, these results clearly suggest that TaPSKR1L-6A mediates resistance to sharp eyespot by activating the expression of several lignin synthesis-related genes and increasing lignin accumulation. Thus, TaPSKR1L-6A is a promising gene for improving wheat resistance against sharp eyespot. This study sheds light on wheat defense mechanisms against R. cerealis.